THE ROLE OF CHILDREN'S FOLKLORE IN THE MORАL EDUCАTION OF ELEMENTАRY STUDENTS (TAMADDUN NURI JURNALI, 2024)
This аrticle discusses the role аnd importаnce of children's folklore pаtterns in the implementаtion of the morаl educаtion of Primаry School students, expаnding their thinking аnd imаginаtion.